Islamic Utopianism and Political Reality: Ali Hasjmy Reconsidered - Marhaban Marhaban (UIN Sunan Kalijaga Yogyakarta, 2021)
This article describes the political philosophy of Ali Hasjmy in formulating the ideal Islamic state. Hasjmy is an intellectual who has produced many works in the topics of politics, literature, and culture that are very useful for the progress and welfare of the Acehnese people and the Indonesian nation in general. The main source of this research is the work and writings of Hasjmy which are directly oriented to politics and the concept of the state. By using analytical content, this article shows several premises on Hasjmy’s utopian visions, which are; First, Muslims should not be anti-politics due to its important in achieving the benefit of the people; Second, the existence of a Islamic state as mandatory; Third, an Islamic state does not have to exist constitutionally but what must exist as Islamic values in a state; Fourth, the importance of obeying the leader; Fifth, every official or government element is responsible for exercising power.